2015
DOI: 10.1186/s12885-015-1512-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of lanreotide in combination with targeted therapies in patients with neuroendocrine tumours in clinical practice: a retrospective cross-sectional analysis

Abstract: BackgroundBased on the mechanism of action, combining somatostatin analogues (SSAs) with mTOR inhibitors or antiangiogenic agents may provide synergistic effects for the treatment of patients with neuroendocrine tumours (NETs). Herein, we investigate the use of these treatment combinations in clinical practice.MethodsThis retrospective cross-sectional analysis of patients with NETs treated with the SSA lanreotide and targeted therapies at 35 Spanish hospitals evaluated the efficacy and safety of lanreotide tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
1
24
0
2
Order By: Relevance
“…This disease-stabilizing activity was confirmed in the randomized phase 3 clinical trial RADIANT-3 (Yao et al 2011), which documented a significantly longer PFS in patients with pNETs randomized to the association of everolimus and octreotide (11 vs. 4.6 months in the octreotide alone arm). In addition, the combination of everolimus with lanreotide suggested efficacy in a retrospective cross-sectional analysis, without unexpected toxicities, apparently through a synergistic effect (Capdevila et al 2015). The possibility of enhanced efficacy with SSAs combined with everolimus is actually being explored in randomized clinical trials, such as the phase 2 study COOPERATE-2 and the LUNA clinical trial, whose definitive results are eagerly awaited, even if preliminary data are disappointing.…”
Section: Tk Receptor Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This disease-stabilizing activity was confirmed in the randomized phase 3 clinical trial RADIANT-3 (Yao et al 2011), which documented a significantly longer PFS in patients with pNETs randomized to the association of everolimus and octreotide (11 vs. 4.6 months in the octreotide alone arm). In addition, the combination of everolimus with lanreotide suggested efficacy in a retrospective cross-sectional analysis, without unexpected toxicities, apparently through a synergistic effect (Capdevila et al 2015). The possibility of enhanced efficacy with SSAs combined with everolimus is actually being explored in randomized clinical trials, such as the phase 2 study COOPERATE-2 and the LUNA clinical trial, whose definitive results are eagerly awaited, even if preliminary data are disappointing.…”
Section: Tk Receptor Growth Factorsmentioning
confidence: 99%
“…Overall, 8 retrospective studies were identified (Bernard et al 2013;Capdevila et al 2015;Ferrer-Garcia et al 2013;Fiebrich et al 2011;Kulke et al 2009;Liu et al 2016;Panzuto et al 2014;Tippeswamy et al 2015), which included a total of 183 patients with pancreatic and 135 patients with extra-pancreatic NETs (see Table 2a). …”
Section: Published Retrospective Studiesmentioning
confidence: 99%
“…The search uncovered eleven relevant randomized prospective studies [9][10][11][12][13][14][15][16][17][18][19] , sixteen nonrandomized prospective studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , and thirteen retrospective studies [36][37][38][39][40][41][42][43][44][45][46][47][48] . Where multiple reports and abstracts were published for a single trial or study, only the most recent full publication was included, unless other reports contained data that were not available in the most recent publication.…”
Section: Primary Literaturementioning
confidence: 99%
“…Several trials included both pnets and non-pnets in their populations w ithout presenting results by subgroup 9,16,19,20,23,25,[35][36][37]39,40,43,44,46 . Because of heterogeneity and a potential for bias, those trials were not used for making the initial recommendations (pnets and non-pnets both respond differently to treatment, making it difficult to draw any conclusions from those trials).…”
Section: Primary Literaturementioning
confidence: 99%
“…Sixty-eight (40%) patients received SSAs in combination with sunitinib and the benefit of the TKI was identified in both groups of treatment. In addition, retrospective results from a Spanish cohort treated with sunitinib (nZ61) or everolimus (nZ73) combined with lanreotide autogel showed interesting results in estimated PFS at 6 and 12 months (79.5 vs 89.3% and 68.6 vs 73% respectively) (48). Pazopanib has also been studied in the phase II trial that firstly introduced the concept of sequential therapy with targeted agents in NETs.…”
Section: Ssas and Targeted Agents In Combinationmentioning
confidence: 99%